KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN HUTANG,DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI SUBSEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Muhamad Alfido B; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to partially and simultaneously examine the effect of institutional ownership, debt policy, and company size on firm value. Where the independent variables in this study are institutional ownership, debt policy, and company size while the dependent variable is the value of the company. The sample used is secondary data derived from the financial statements of chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2011 to 2015. This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling techniques. Data analysis using multiple linear regression analysis, t test, F test, and the coefficient of determination test. Data analysis uses multiple linear regression analysis. The results of this study indicate that the variable institutional ownership, partial debt policy (t test) does not affect the value of the company while the size of the company partially influences the value of the company in manufacturing companies in the chemical subsector which are listed on the Indonesia Stock Exchange. Simultaneous test results (F) indicate the influence of institutional ownership variables, debt policy, and company size on the value of the company in chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange. Key Words : institutional ownership, debt policy, company size, and company value